Remittances and Their Socioeconomic Effects on Rural Bangladesh: A Case Study of Migrants in Malaysia - Horaira, Gazi Abu; Islam, Rabiul; Shariffuddin, Mohd Dino Khairri (International Journal of Economics and Financial Issues, 2025)
International migration has notable socioeconomic impacts, particularly through remittance transfers sent by migrant workers to their home countries. Since the mid-1970s, labor migration has significantly affected the socioeconomic conditions of numerous Bangladeshi households. The flow of remittances is a complex phenomenon that influences economic, social, legal, and cultural aspects at both national and global levels. Many developing countries have studied the consequences of this phenomenon, and this research focuses on the influence of the household head’s connection to the migrant in rural Bangladesh. The study was conducted using microeconomic data collected from a survey of 350 rural households in 15 villages. The survey was conducted between September 2023 and August 2024. Statistical analysis was used to explore the relationship between the household head’s connection to the migrant and the factors that influence remittances, as well as the socioeconomic effects on the receiving households. The analysis revealed that the relationship between the household head and the migrant—whether father, mother, spouse, or brother—showed variability in both the motivations for sending remittances and the socioeconomic impacts in the rural areas. The factors affecting remittances and their resulting impacts varied depending on the household head’s relationship with the migrant and the community’s connections. Discrimination based on the household head’s local relationships also influenced the socioeconomic effects of the remittances.